2004
DOI: 10.1523/jneurosci.1074-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AMPA Receptor Gating in the Development of High-Fidelity Neurotransmission at the Calyx of Held Synapse

Abstract: During early postnatal development of auditory synapses, the decay time course of AMPA receptor (AMPAR) EPSCs accelerates markedly, but the mechanisms underlying this process remain uncertain. Using the developing calyx of Held synapse in the mouse auditory brainstem, we have examined presynaptic and postsynaptic elements that may regulate decay kinetics of AMPAR EPSCs. We found that the decay time kinetics was voltage dependent in both immature and mature synapses, being slower at positive potentials than neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
102
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 69 publications
19
102
1
Order By: Relevance
“…The calyx of Held synapse, at maturity, is capable of phaselocking postsynaptic firing to presynaptic input at high rates, as a result of multiple adaptations (Wang and Kaczmarek, 1998;Trussell 1999;Joshi and Wang, 2002;von Gersdorff and Borst, 2002;Joshi et al, 2004). In line with previous evidence showing a developmental increase in the efficiency of exocytosis (Taschenberger et al, 2002), we suggest that tight coupling between VGCCs and vesicles may represent a critical adaptation that ensures a strong synaptic drive for high-fidelity neurotransmission with minimal jitter in synaptic delay.…”
Section: Discussionsupporting
confidence: 85%
“…The calyx of Held synapse, at maturity, is capable of phaselocking postsynaptic firing to presynaptic input at high rates, as a result of multiple adaptations (Wang and Kaczmarek, 1998;Trussell 1999;Joshi and Wang, 2002;von Gersdorff and Borst, 2002;Joshi et al, 2004). In line with previous evidence showing a developmental increase in the efficiency of exocytosis (Taschenberger et al, 2002), we suggest that tight coupling between VGCCs and vesicles may represent a critical adaptation that ensures a strong synaptic drive for high-fidelity neurotransmission with minimal jitter in synaptic delay.…”
Section: Discussionsupporting
confidence: 85%
“…2 D) ( p Ͻ 0.01). These results are similar to those reported recently in mice (Joshi et al, 2004). From P14 to P21, however, neither the desensitization time constants nor the deactivation time constant changed significantly (Fig.…”
Section: Developmental Speeding Of Desensitization and Deactivationsupporting
confidence: 92%
“…In contrast, Joshi et al (2004) reported that GluR2 immunoreactivity is virtually absent in MNTB neurons in mice throughout development (P5-P18). Consistent with GluR2 deficiency, in mice the current-voltage relationship of AMPA-EPSCs shows a strong rectification with little outward current in the presence of intracellular spermine in the MNTB neurons (Joshi et al, 2004). In contrast, in rats GluR2 immunoreactivity was present throughout development both in the synaptic and extrasynaptic regions of MNTB neurons (supplemental Fig.…”
Section: Developmental Changes In the Glur Transcriptsmentioning
confidence: 88%
See 1 more Smart Citation
“…Such differences in the decay or deactivation of NGIC responses can profoundly impact the window of synaptic excitability and integration (4,7,8). Control over NGIC kinetics is also a powerful force during development, where slower receptor subtypes tend to be used early on, broadening the window of plasticity during critical periods, and later give way to faster decaying subunits providing greater temporal precision (9)(10)(11)(12)(13). This trade-off between the window of integration on the one hand and temporal precision on the other persists in the mature brain.…”
mentioning
confidence: 99%